A linear programming approach for hybrid flexible flow shop with sequence-dependent setup times to minimise total tardiness. Issue 1 (2021) - Oujana, S.; Yalaoui, F.; Amodeo, L.
Abstract: In this study, we consider a particular version of the hybrid flexible flow shop (HFFS) scheduling problem, inspired from a real-life application in a printing industry. The considered problem is a variation of the classical Flow shop problem, in which specific constraints are jointly considered, such as non-identical parallel machines, sequence-dependent setups on machines, machine eligibility, and precedence constraints among jobs, in order to minimize the total tardiness time. After a problem description, a mathematical model, in form of mixed integer linear programming (MILP) model, that incorporates these aspects is developed and evaluated using ILOG Cplex software.